Method for Determining Critical Slip Surface of Cohesive Soil Slope Based on the Principle of Simple Penetration Test - Zhang, Aiqing; Li, Jinyun; Zhang, Youheng (Advances in Civil Engineering, 2021)
In order to propose a new method for determining the critical slip surface of the cohesive soil slope, the relational expression between the number of simple penetration and slope bearing capacity is established on the basis of studying the principle of the simple penetration test with reference to the research result concerning the number of standard penetration and bearing capacity of foundation soil. The measuring points are arranged at the slope of a certain road slope according to the actual conditions, to measure the number of simple penetration, calculate the slope bearing capacity at different depths with the relational expression, draw the curve of slope bearing capacity changing with the depth, search the points of abrupt change in slope bearing capacity to get the arc curve of abrupt change points, and then determine the critical slip surface of slope. The test results are compared with the results calculated by the finite element method (FEM) and theoretical method, to verify the feasibility and rationality of the simple penetration method. The research results show that the simple penetration method is applicable to and capable of quick and accurate determination of critical slip surface of the cohesive soil slope, thus providing a new method for analyzing the slope stability of cohesive soil.